Propofol Ketamine versus Propofol Fentanyl for Day Care Surgeries Comparison of Postoperative Recovery - Hiranand, Gotam Kumar, Ravi Kumar, Mubarak Shah, Muhammad Mobashir-Ul-Haque, Udesh Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Intravenous anaesthetic should result in early discharge and rapid recovery with minimum side-effects. Propofol is considered gold standard in day care surgeries. Ketamine and fentanyl can also be used but they have several disadvantages including postoperative vomiting and nausea, emergence delirium and prolonged recovery. Aimed: To compare mean recovery between propofol-ketamine and propofol fentanyl in day care surgeries. Study Design: Single blinded randomized control study. Place and Duration of Study: Department of Anaesthesiology, The Indus Hospital Karachi from 1st January to 31st May 2019. Methodology: Sixty patients (30 in each group) with ASA grade I-II who had undergone elective day care surgery, 20 to 60 years of age of either gender were included at a tertiary care setup. In patients of Arm1, the induction of anesthesia was done with ketamine (1.0 mg/kg body wt) and propofol (1.0 mg/kg body wt.) given in IV line. In patients of Arm2, anesthesia induction was done with fentanyl (2.0 µg/kg body wt.) and propofol (1.5 mg/kg body wt.) given in IV doses. A pre-designed pro forma was used to record information of patients. Dexamethasone 0.1mg/kg body weight was used as antiemetic. Results: Mean age of the patients at the time of surgery was 34.57±32 years with no significant difference in mean age between Arm-1 and Arm-2 (34.4±11.5 vs 34.7±11.2 respectively, p-value=0.902). Overall Median Modified steward recovery score at 5, 10 and 15 minutes was (Med (IQR): 8(7-9), 9(8-9) and 9(9-9) respectively). Moreover, Analysis shows that there is no significant difference in median Modified steward coma score at 5, 10 and 15 minutes between both Arms. Conclusion: The mean recovery score is less after propofol-ketamine use in day care surgeries as compared to propofol fentanyl use.